2021
DOI: 10.1002/cbic.202100028
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Surrogate‐Constrained Dynamic Antiparallel β‐Sheets

Abstract: Antiparallel β‐sheets are important secondary structures within proteins that equilibrate with random‐coil states; however, little is known about the exact dynamics of this process. Here, the first dynamic β‐sheet models that mimic this equilibrium have been designed by using an H‐bond surrogate that introduces constraint and torque into a tertiary amide bond. 2D NMR data sufficiently reveal the structure, kinetics, and thermodynamics of the folding process, thereby leading the way to similar analysis in isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It is the only HBS model to mimic the 3 10 -helical turn 52 . Moreover, we have also shown that our HBS model has also been applied in studying dynamic β-sheet structures 53 . Thus, this HBS model is a generic replacement for H-bonds in a variety of turns (Figure 1).…”
Section: Introductionmentioning
confidence: 81%
“…It is the only HBS model to mimic the 3 10 -helical turn 52 . Moreover, we have also shown that our HBS model has also been applied in studying dynamic β-sheet structures 53 . Thus, this HBS model is a generic replacement for H-bonds in a variety of turns (Figure 1).…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, developing a novel template to study this transition is essential for tackling the early stage of diseases caused by amyloid formation. A propyl‐linked HBS‐model dipeptide has been recently reported to study this transition [45] . The torque generated by the tertiary amide bond was employed to determine the equilibrium between the β‐sheet and non‐β‐ sheet conformations.…”
Section: Hbs‐model As Mimicry Of Different Secondary Structuresmentioning
confidence: 99%
“…Olefin [43] β-Hairpin NA TQTRAPGDEkITFG-NH 2 Thioether [44] β-Hairpin NA AG-iBu Propyl [45] β-sheet NA After helix, β-hairpin is the most abundant secondary structure of the proteins involved in several PPIs. [55,56,57] Apart from stabilizing different types of helices, the olefin HBS-model is also capable of mimicking the β-turn conformation.…”
Section: Afgve-iprmentioning
confidence: 99%
See 2 more Smart Citations